Analisis Sifat Fisik dan Daya Terima Bubble (Tapioca Pearl) dengan Penambahan Puree Bit (Beta Vulgaris) - Qoyyima, Najmi Tsabita; Mahdiyah, Mahdiyah; Alsuhendra, Alsuhendra (Advances In Social Humanities Research, 2024)
The innovation of making bubble with the addition of beet puree can be one way to improve the quality of texture, taste and nutrition of bubble. To get a chewy bubble texture, it require a long boiling time to cook through inside. One way to reduce this weakness is to use beetroot as the raw material for bubble. Beetroot have a high starch content which causes increased elasticity in the dough. The starch contained in beets really helps the starch gelatinization process. The method used is an experimental method with three types of treatment, which bubble with the addition of 60%, 80% and 100% beet puree. The validity test conducted using organoleptic tests on five expert panelists with six aspects, that is color, chocolate aroma, beet aroma, sweetness, beet taste and texture. Based on the results of the analysis, bubble with the addition of 60% beet puree is superior in various aspects of assessment so it is concluded that bubble with the addition of 60% beet puree is the product with the best organoleptic quality. Physical test is done by measuring the weight and diameter of the bubble before and after boiling with 3 repetitions. The analysis results showed that the average bubble weight is 457.3 mg, while the average bubble diameter is 8.74 mm. Consumer acceptence test was conducted using hedonic test (favorability test) on 30 panelists. The results of the favorability test showed that bubble with the addition of 100% beet puree was most liked. Analysis result show that the addition of beet puree to bubble has no real effect or difference.